Analysis of Factors of Service Quality on Patient Satisfaction in the Outpatient Clinic of Bhayangkara TK Hospital. III Pekanbaru, Riau Police: Analisis Faktor-Faktor Kualitas Pelayanan Terhadap Kepuasan Pasien Di Poli Rawat Jalan Rumah Sakit Bhayangkara TK. III Pekanbaru Polda Riau - Sari Mustika Dewi; Welly Sando; Ahmad Satria Efendi (Badnur Medisa Group, 2022)
The dimension of service quality is very important from the patient’s perpective as indicated by the presence of patient satisfaction which has a significant relationship which has a significant relationship with the dimensions of physical evidence, reliability, responsiveness, assurance, and empathy. The purpose of this study was to determine the Analisys of service quality factors on factors on patient satisfaction in outpatient polyclinic at Bhayangkara Hospital TK. III Pekanbaru Polda Riau. Technique of the study This is a study quantitatively by using design research analytic with design cross-sectional. Research is carried out at Bhayangkara Hospital TK. III Pekanbaru Polda Riau with sample 116 respondents. The sampling technique used is using the Lemeshow formula. Tools measure that is used is the questionnaire. Data analysis consists of univariate analysis and bivariate with test Chi-square. The results of the study show that the majority of respondents aged 56-75 years (late elderly) were 87 respondents (75,0%), the majority of respondents have high school education as many as 38 respondents (32,8%), the majority of respondents work privately as many as 51 respondents (44,0%), the majority of respondents are female as many as 74 respondents (63,8%), the majority of respondents with poor Responsiveness (Responsiveness) were 67 respondents (57,8%), the majority of respondents with Competence (Competence) were 68 respondents (58,6%), the majority of respondents with Tangible (Tangible) were 63 respondents (54,3%), the majority of respondents with communication (communication) were 68 respondents (58,6%). There is a significant effect between Responsiveness (Responsiveness) and patient satisfaction, where p value < 0,05 is 0,038, There is a significant effect between Competence (Competence) and patient satisfaction, where p value < 0,05 is 0,039, There is a significant effect between Tangible (Tangible) and patient satisfaction, where p value < 0,05 is 0,018, and There is a significant effect between Competence (Competence) and patient satisfaction, where p value < 0,05 is 0,039, There is a significant effect between communication (communication) and patient satisfaction, where p value < 0,05 is 0,029.